ANALISIS USER INTERFACE DAN USER EXPERIENCE SERTA REDESIGN APLIKASI MAXIM MENGGUNAKAN METODE DESIGN THINKING - Livia Ramadhani (2023)
The current technological advancements have led to an increased societal use of applications, prompting transport companies to devise online transport systems for the convenience of customers. Maxim is an online transport application that provides services in the realm of transport and delivery. Based on its App Store ratings, Maxim has a notably high rating of 4.9 out of 5. However, a significant number of user reviews suggest difficulties and complaints while using the Maxim application, such as a confusing interface and unappealing design among other issues. Thus, this study was conducted to assess the quality of the user interface (UI) and user experience (UX) of the current Maxim application and to redesign its application design to address user challenges, enhance its functionalities, and foster its utility. The System Usability Scale (SUS) method was employed for the analysis of the current application's UI and UX, and the design thinking method was adopted for the redesign of the Maxim application. According to the study, the analysis of the current system scored 42.1, and after the redesign, the score increased to 74.5, indicating an improvement of 32.4%. This significant increase is anticipated to refine the application further, fulfilling user requirements and resolving issues faced by Maxim application users.